2013
DOI: 10.1093/icvts/ivt156
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial fistula after lobar size reduction for bilateral lung transplantation in Kartagener's syndrome: a surgical challenge

Abstract: Bilateral lung transplantation was performed in a 52-year old man with end-stage Kartagener's syndrome. A postimplantation right lower lobectomy was required for volume reduction and dextrocardia. A bronchial fistula developed with an intractable colonized residual pleural cavity. Closure was obtained successfully with multiple-stage procedures including decortication, muscle flap and an open-window thoracostomy without modification of the immunosuppressive protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…In the current study, brain-dead donor lobar lung transplantation demonstrated excellent early and late post-transplant outcomes in comparison with standard lung transplantation using full-sized grafts. However, life-threatening bronchial complications such as bronchial fistula have been reported in lobar lung transplantation [ 11 , 12 ]. We performed lobar-to-lobar bronchial anastomoses to avoid leaving donor bronchial stumps closed, and thus there were no bronchopleural fistulae after brain-dead donor lobar lung transplantation (since initiating these types of transplantations, we have not had a patient experience bronchopleural fistulae).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, brain-dead donor lobar lung transplantation demonstrated excellent early and late post-transplant outcomes in comparison with standard lung transplantation using full-sized grafts. However, life-threatening bronchial complications such as bronchial fistula have been reported in lobar lung transplantation [ 11 , 12 ]. We performed lobar-to-lobar bronchial anastomoses to avoid leaving donor bronchial stumps closed, and thus there were no bronchopleural fistulae after brain-dead donor lobar lung transplantation (since initiating these types of transplantations, we have not had a patient experience bronchopleural fistulae).…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] However, life-threating complications, including bronchial fistula, have been reported. 17,18 Our techniques of bronchial management are unique in that we allow leaving a recipient's bronchial stump and avoid leaving donor bronchial stumps by using lobar-to-lobar bronchial anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…3 Brioude and associates mentioned that the surgical procedure of KS patients does not seem to require specific technical modifications when performed with lungs provided by a normal donor. 1 Similarly, Graeter and associates performed a double lung transplant for KS and emphasized that no technical modifications were necessary. 2 Despite the successful experiences of these authors, we do not agree with them; anatomic obstacles may have seen.…”
Section: Discussionmentioning
confidence: 99%
“…Kartagener syndrome (KS) is an uncommon, congenital, genetic disorder characterized by bronchiectasis, situs inversus totalis thoracalis et abdominalis, immotile cilia, chronic sinusitis, and infertility. 1,2 Lung transplant is a treatment option for terminal-stage bronchiectasis. We present a case of KS, to highlight the importance of related anatomic variations pitfall that may influence the decision for patient selection and may complicate the course of the operation.…”
Section: Introductionmentioning
confidence: 99%